A BOOST RECTIFIER FOR LOW-VOLTAGE ENERGY HARVESTING APPLICATIONS VISHNU PRASAD (International Journal of Engineering Sciences & Management Research, 2016)
In this paper, a single-stage ac–dc power electronic converter is proposed to efficiently manage the energy harvested from electromagnetic micro scale and mesoscale generators with low-voltage outputs. The proposed topology combines a boost converter and a buck-boost converter to condition the positive and negative half portions of the input ac voltage, respectively. Only one inductor and capacitor are used in both circuitries to reduce the size of the converter. A 2 cm × 2 cm, 3.34-g prototype has been designed and tested at 50-kHz switching frequency, which demonstrate 71% efficiency at 54.5 mW. The input ac voltage with 0.4-V amplitude is rectified and stepped up to 3.3-V dc. Detailed design guidelines are provided with the purpose of minimizing the size, weight, and power losses. The theoretical analyses are validated by the experiment results.